Comparison of oxygen enriched and oxy-combustion characteristics of lignite in a CFB: Modelling and experimental verification - YILMAZ, BARIŞ; ÖZDOĞAN, ZEYNEP SİBEL (ELSEVIER, 2021)
Oxy-combustion and oxygen enriched combustion are considered as promising options for CO2 capture and storage. In the present study, numerical simulations of a 30 kWth circulating fluidized bed reactor were performed under oxygen enriched (O-2/N-2) and oxy-combustion (O-2/Recycled Flue Gas) (RFG) conditions to investigate the effects of combustion atmospheres on the lignite combustion characteristics. The influence of oxygen concentration ranging from 21% to 28% on temperature and gaseous emissions were investigated by keeping excess oxygen ratio constant at 1.45 for both atmospheres. The predicted gas emissions and temperature profiles along the combustor were validated with conducted experiments. A good agreement between the simulated and measured data was achieved. CO2 emission was found more in O-2/RFG combustion compared to O-2/N-2 mode. All gas emissions increased with oxygen enrichment except for CO in both cases. O-2/RFG case appears to be more promising option considering emission amounts per unit energy input. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Oxy-combustion; Oxygen enriched; CFB; Modelling; CPFD; Validation; CIRCULATING FLUIDIZED-BED; GAS-SOLID FLOW; FUEL COMBUSTION; COAL COMBUSTION; BITUMINOUS COAL; CO2 CAPTURE; SIMULATION; PARTICLES